Analisis Kemandirian Keuangan Daerah dalam Konstribusinya bagi Kesejahteraan Masyarakat Kabupaten Bandung Tahun 2019-2021 - Azzahra, Allifia; Armeliza, Diah; Musyaffi, Ayatulloh Michael (LPPM Universitas Negeri Jakarta, 2024)
This study aims to analyze regional financial independence as measured using financial independence ratios in accordance with the Regulation of the Minister of Home Affairs Number 19 of 2020, analyze the condition of community welfare, especially in the fields of health, independence, employment and education and analyze how financial independence contributes to community welfare. This research takes the Bandung Regency Government as the object of research. In the data collection technique, this study uses secondary data, namely the LKPD of the Bandung Regency Government for 2019-2021 using descriptive quantitative methods. The results of this study indicate that the regional financial independence of the Bandung Regency Government is considered insufficient. This is indicated by the nominal regional financial independence of the Bandung Regency Government of 17.89 for 2019, 19.07% for 2020 and 19.05% for 2021. The welfare of the people of Bandung Regency in terms of health which has appropriate standards by having one or more health facilities in each existing sub-district, in terms of poverty, the percentage of poor people who have increased is lower than the average increase in the percentage of poor people in districts / cities in West Java, In terms of employment, which experienced an increase in the Labor Force Participation Rate (TPAK) in 2021 which was greater than the average increase in TPAK in districts / cities in West Java, in terms of education, the level of Pure Participation Rate (APM) which managed to increase. As for its contribution to community welfare, the Bandung Regency Government allocates expenditures, especially to related agencies. This allocation is channeled in the form of organizing programs and activities aimed at improving welfare. However, if reviewed through the independence of regional finances, the Bandung Regency Government still shows